2017
DOI: 10.1007/s10439-017-1863-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Inter-Erythrocyte Forces with Ultra-High Frequency (410 MHz) Single Beam Acoustic Tweezer

Abstract: Efforts on quantitative measurements of the interactive forces of red blood cells (RBC) have been pursued for many years in hopes of a better understanding of hemodynamics and blood rheology. In this paper, we report an approach based on an ultra-high frequency (410 MHz) single beam acoustic tweezer (SBAT) for quantitative measurements of inter-RBC forces at a single cell level. The trapping forces produced by this ultra-high frequency (UHF) SBAT can be quantitatively estimated with a micropipette. Since the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…10log 10 R = −2.00 dB (4) 10log 10 T = −4.34 dB (5) RT loss = 5.33 dB. The experimental conversion loss is higher (worse) than that of theoretical prediction because the sound axis between the silica glass buffer rod and reflection plate was deviated.…”
Section: A Transducer Performance In Water Mediummentioning
confidence: 94%
See 1 more Smart Citation
“…10log 10 R = −2.00 dB (4) 10log 10 T = −4.34 dB (5) RT loss = 5.33 dB. The experimental conversion loss is higher (worse) than that of theoretical prediction because the sound axis between the silica glass buffer rod and reflection plate was deviated.…”
Section: A Transducer Performance In Water Mediummentioning
confidence: 94%
“…One is to thin down single crystal plates and the other is to grow thick piezoelectric films. Lim and Shung [5] reported the 7.1-μm-thick polished LiNbO 3 single crystal focused transducer operating at 410 MHz for the evaluation of interactive forces of red blood cells. Chen et al [6] reported the mechanically polished LiNbO 3 single crystal focused transducer operating at 526 MHz for microparticle manipulation applications.…”
Section: Introductionmentioning
confidence: 99%
“…The internal construction of the BTB transducer is shown in Figure 1 b. The transducers were fabricated through the following procedure for creating a high-frequency transducer [ 34 , 35 , 36 , 37 , 38 ]. The optimized aperture size and thickness of the piezoelectrical material and the matching layer thickness for the individual imaging and therapeutic transducers were simulated with the Krimholtz, Leedom, and Matthaei models (PiezoCAD, Sonic Concepts, Bothell, WA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, acoustic tweezers have garnered increased interest from the biomedical research community, as they can perform noncontact, label-free, and precise manipulation of bioparticles (1,(8)(9)(10)(11). With these merits, acoustic tweezers have been used in a wide range of biomedical applications, including patterning and printing cells (12)(13)(14)(15), separating and sorting cells (16)(17)(18)(19), controlling cell-cell interactions (20,21), single-cell analysis (22)(23)(24), concentrating bioparticles (25)(26)(27)(28)(29)(30)(31), acousto-mechanical phenotyping (32,33), constructing tissues (34)(35)(36)(37)(38), generating and translating droplets (39)(40)(41), rotating multicellular organisms (42,43), and isolating extracellular vesicles (44,45).…”
Section: Introductionmentioning
confidence: 99%